2022
DOI: 10.2147/idr.s372420
|View full text |Cite
|
Sign up to set email alerts
|

Potential Predictive Value of miR-125b-5p, miR-155-5p and Their Target Genes in the Course of COVID-19

Abstract: Purpose This study aimed to provide new biomarkers for predicting the disease course of COVID-19 by analyzing the dynamic changes of microRNA (miRNA) and its target gene expression in the serum of COVID-19 patients at different stages. Methods Serum samples were collected from all COVID-19 patients at three time points: the acute stage, the turn-negative stage, and the recovery stage. The expression level of miRNA and the target mRNA was measured by Quantitative Real-Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Collected data showed that of these, most of the studies were published during the year 2021 ( n = 16), 53–68 followed by 2022 ( n = 15), 69–83 with the least numbers in the year 2020 ( n = 4) 53,84–87 (Figure 2a). Although the selected studies were published globally, most of them were reported from China ( n = 8), followed by Italy ( n = 7), Spain ( n = 4), and USA ( n = 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collected data showed that of these, most of the studies were published during the year 2021 ( n = 16), 53–68 followed by 2022 ( n = 15), 69–83 with the least numbers in the year 2020 ( n = 4) 53,84–87 (Figure 2a). Although the selected studies were published globally, most of them were reported from China ( n = 8), followed by Italy ( n = 7), Spain ( n = 4), and USA ( n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…Table represents the summary of the total number of reported miRNAs in different COVID‐19 severity stages. It should be noted that most of the groups included in this network were reported in only one or two studies: S/MO vs C, 69 S vs MO, 73,86 MO vs C, 86 SR vs DS, 77 SC vs MM, 61 S vs MO vs MI, 78 MO vs MI, 73 S vs MI, 60,75,78,82 S/MI vs C, 84 RE vs Inf 81 ) except “Inf vs C” and “S vs C”. Initially, this network contained 71 miRNAs from 23 studies.…”
Section: Resultsmentioning
confidence: 99%
“… [ 116 ] miR-28-3p In vitro 293 T cells Disintegrin and ADAM17 Exerts its function on both cell viability and cell apoptosis (Inhibit miR-28-3p expression inhibited cell viability and promoted cell apoptosis during S-protein treatment) [ 117 ] miR-31, miR-29, miR-126, and miR-17 Bioinformatics In vitro Human serum samples ZMYM5, COL5A3, and CAMSAP1 These miRNAs have been down-regulated and the levels of their mRNA targets have been enhanced with the increase of disease grade [ 118 ] miR-148a In vitro HEK-293T and CHME3 USP33, IRF9, TNFα, NF-κB, and IFN-β Activate human microglia [ 119 ] let7b‐5p In vitro Naso‐oropharyngeal swabs and ATCC ACE2 and DPP4 Participates in the mechanisms of acquiring the virulence of the virus and perform as a therapeutic target for COVID‐19 [ 120 ] miR-125b-5p and miR-155-5p In vitro Human serum samples CDH5, STAT3, and TRIM32 Participates in the mechanisms of acquiring the virulence of the virus. Could be useful a novel potential biomarkers to predict the time nodes of the acute, turn-negative, and recovery stages of virus [ 121 ] miR-32-5p, miR-98-3p, miR-423-3p, and miR-1246 Bioinformatics In vitro Human serum samples ACE2 and RAB14 Could be taken as potential biomarkers of COVID-19 progression as well as candidates for future therapeutic approaches. Relates to viral infection, inflammatory response, and coagulation-related processes [ 122 ] miR-29a-3p RNA-Seq analysis In vitro …”
Section: Genetic Markers Of Severe Covid-19mentioning
confidence: 99%
“…These data provide a molecular explanation for the resistance of monocytes to COVID-19 infection and support the notion that innate immunity mediated by intracellular miRNAs may play a significant role in protecting cells of the immune system from COVID-19 infection. A brief summary of the major miRNAs and their regulatory effects involving signal pathways of COVID-19 mechanism is shown in Table 1 [ [115] , [116] , [117] , [118] , [119] , [120] , [121] , [122] , [123] , [124] ].
Fig.
…”
Section: Non-coding Rnas In Covid-19mentioning
confidence: 99%
“…The basic characteristics of the 16 [1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17] included articles are shown in Table 1. All of them were case-control studies.…”
Section: Basic Characteristics and Quality Of The Literaturementioning
confidence: 99%